The Revitalization of Makassar Urban Drainage System Based on Eco Drainage Retention Pond - Karamma, Riswal; Lopa, Rita Tahir; Hatta, Mukhsan Putra (INTEK: Jurnal Penelitian, 2021)
One of the causes of flooding in Makassar City is the management of the water system that is not optimal. It is necessary to arrange a drainage system to overcome flooding in Makassar City. In this study the topography on Catchment area analysis, analysis of hydrology and hydraulics analysis. Modeling the distribution of flood performed using HEC-RAS applications. This research was conducted in the Tallo watershed which consists of the Upper Tallo sub-watershed and the Mangalarang sub-watershed. The results of the analysis of flood discharge in the Tallo Hilir sub-watershed are 523.76 m3/s and in the Mangalarang sub-watershed are 886.82 m3/s. The flood overflow of the Tallo River spread over 6.48 km2 of Manggala District, 0.31 km2 of Rappocini District, 4.24 km2 of Panakukang District, 3.37 km2 of Tallo District, 11.59 km2 of Tamalanrea District and 0.01 km2 of Biringkanaya District. The total area of flood distribution is 26 km2. The solution to overcome the flooding of the Tallo River with an environmentally sound drainage system, it is necessary to plan the construction of a retention pond in Tamalanrea District, with a normal total storage volume of 2.48 million m3 and a maximum capacity of 5.31 million m3. The construction of this retention pond can reduce 17.7 km2 of flood-affected area.